Ethics and Democracy in Access to Food. The Venezuelan Case - Marrero Castro, Juan Fernando; García, María José Iciarte (Frontiers in Sustainable Food Systems, 2021)
The humanitarian emergency that Venezuela is experiencing, one of whose edges is the food insecurity of more than 80% of the population, coincides with the serious institutional deterioration of the country and with the rupture of the constitutional order under the so-called “socialism of the 21st century” (1999 to the present), as reflected in various reports, including that of the United Nations High Commissioner for Human Rights. Access to food as a fundamental human right is better valued and guaranteed in democracies, where free media and independent public powers function as counterweights to the central executive power and act as effective instruments for correcting the wrong policies in food and nutritional matters, and officials responsible for direct and indirect damages to the general population or to vulnerable groups, are sanctioned. This topic has been studied by Nobel laureate Amartya Sen. In functional democracies, the ethical dimension of the right to food is also better guaranteed, since this right is realized not only by ensuring sufficient, balanced and healthy food, to meet the nutritional needs of the population, but that food is supplied in a culturally acceptable manner and seeking ways, mechanisms and procedures that are not contrary to the dignity of human beings. As a human right, the State has the greatest responsibility in guaranteeing the right to food, but not to fulfill a mere welfare duty or as a benefactor, but to guarantee that no one suffers from hunger or severe malnutrition, providing safe, nutritious and sufficient food, to those who cannot do it themselves, prevent all forms of discrimination in access to food or resources that are used to produce them, such as land, and take measures to ensure that families and their members can feed themselves in a dignified manner. As the Venezuelan regime closed the door to freedoms, malnutrition, hunger and non-fulfillment of the right to food also grew, according to FAO reports and Sen's assumptions under these scenarios seem to hold in the country.